PENGARUH PEMBERIAN PUPUK UREA DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays Saccharata Sturt.L) Varietas Gendis - Hidayah, Umur; Puspitorini, Palupi; Setya, Agung (Universitas Islam Balitar, 2016)
This research have go to influence interaction between urea fertilizer and chicken manure, also best small boxist to growing and result Sweet corn (Zea mays saccharata sturt . L) gendis's variety . This research is done with to use it Group Random Planing that be arranged according to Factorial (RAKF) with 2 factor, first factor that is urea's fertilizer (U) that consist from 3 level that is urea 0 Kg/ha (U0 /control), urea 100 Kg/ha (U1), urea 200 Kg/ha (U2), urea 300 Kg/ha (U3). second Factor that is chicken manure (A) consist from 3 level that is : chicken manure 0 Kg/ha (A0 /control), chicken manure 10 Ton/ha (A1), chicken manure 20 Ton/ha (A2). Variable that to be perceived to cover high of plants, leaf number, heavy , long of tuna and tuna diameter. The data is analyzed with to use it Analisis Of Varian (ANOVA), if influency to be continued with test DMRT 5%. Research result to show that : 1). Interaction between urea's fertilizer 200 kg/ha and chicken manure 20 ton/ha give it best influence in growing and plants result sweet corn. 2 ) fertilizer Giving urea 200 kg/ha gave best influence in growing and plants result sweet corn. 3). the Giving of chicken manure 20 ton/ha give it best influence in growing and plants result sweet corn